Regional facial asymmetries in unilateral orofacial clefts - Kuijpers, Mette A.; Desmedt, Dries J.; Nada, Rania M.; Bergé, Stefaan J.; Fudalej, Piotr S.; Maal, Thomas J. (European journal of orthodontics, 2015)
Assess facial asymmetry in subjects with unilateral cleft lip (UCL), unilateral cleft lip and alveolus (UCLA), and unilateral cleft lip, alveolus, and palate (UCLP), and to evaluate which area of the face is most asymmetrical. Standardized three-dimensional facial images of 58 patients (9 UCL, 21 UCLA, and 28 UCLP; age range: 8.6-12.3 years) and 121 controls (age range 9-12 years) were mirrored and distance maps were created. Absolute mean asymmetry values were calculated for the whole face, cheek, nose, lips, and chin. One-way analysis of variance, Kruskal-Wallis, and t-test were used to assess the differences between clefts and controls for the whole face and separate areas. Clefts and controls differ significantly for the whole face as well as in all areas. Asymmetry is distributed differently over the face for all groups. In UCLA, the nose was significantly more asymmetric compared with chin and cheek (P = 0.038 and 0.024, respectively). For UCL, significant differences in asymmetry between nose and chin and chin and cheek were present (P = 0.038 and 0.046, respectively). In the control group, the chin was the most asymmetric area compared to lip and nose (P = 0.002 and P = 0.001, respectively) followed by the nose (P = 0.004). In UCLP, the nose, followed by the lips, was the most asymmetric area compared to chin, cheek (P < 0.001 and P = 0.016, respectively). Despite division into regional areas, the method may still exclude or underrate smaller local areas in the face, which are better visualized in a facial colour coded distance map than quantified by distance numbers. The UCL subsample is small. Each type of cleft has its own distinct asymmetry pattern. Children with unilateral clefts show more facial asymmetry than children without clefts.